Improving Nutrient Efficiency as a Strategy to Reduce Nutrient Surpluses on Dairy Farms - C.J.M. Ondersteijn; A.G.J.M. Oude Lansink; G.W.J. Giesen; R.B.M. Huirne (The Scientific World Journal)
Dutch nutrient policy aims at reducing leaching of agricultural nutrients by internalizing the negative externalities associated with inefficient nutrient use. This is done by taxation of nitrogen and phosphate surpluses that exceed a hectare-based threshold of maximum-allowed surpluses. One management strategy farmers may use to reduce the nutrient surpluses on their farms is to improve the nutrient efficiency of the agricultural production process. This study employs Data Envelopment Analysis (DEA) to calculate nitrogen and phosphate efficiencies and an overall nutrient efficiency measure for a 3-year panel of 114 Dutch dairy farms. Subsequent analyses show the impact of both farm intensity and nutrient efficiency on the nitrogen and phosphate surpluses. It appears that farm intensity has a positive effect on efficiency, but efficiency and intensity exert opposite influences on nutrient surpluses. This is especially the case for nitrogen. The magnitude of a possible reduction of nitrogen surpluses through a strategy of efficiency improvement is therefore limited by the intensity of the farming system, unless the technology with which nutrients are used by the farming system can be further improved or input/output ratios will be altered.